Designing of electronic terminological dictionary on pharmaceutical chemistry - O E Sattarova (RUDN Journal of Medicine, 2010)
The electronic terminological dictionary on pharmaceutical chemistry was developed. The peculiarities of desinging of the dictionary and steps of its creation were explored. The electronic terminological dictionary was tested during academic competition on pharmaceutical chemistry. The created dictionary was admitted to use as an electronic educational resource on chair of pharmaceutical chemistry of full-time department.